Intravitreal Aflibercept Has Long-Term Benefits in Treatment of DME - Hoyle, Brian (MD Conference Express, 2014)
This article describes the 2-year outcomes of the Intravitreal Alfibercept Injection in Vision Impairment Due to DME [VIVID; NCT01331681] trial as well as the Study of Intravitreal Administration of VEGF Trap-Eye (BAY86-5321) in Patients With Diabetic Macular Edema [VISTA; NCT01363440]. VIVID and VISTA are both phase III, randomized, double-blind global studies in which intravitreal aflibercept was injected to treat diabetic macular edema.